A Review of Global Occurrence of Emerging Pollutants in Wastewater: Present Status, Source/Pathway, Extraction and Detection Techniques - (:unkn) unknown (My University, 2023)
The occurrence of emerging pollutants (EPs) is constantly reported around the world. Despite this, due to their large number, only a few of these compounds have been toxicologically evaluated. In this paper, the literature on EPs found in wastewater was reviewed from 1998 to 2021, with a focus on their occurrence, extraction, and detection methods. Pesticides, microplastics, pharmaceuticals and personal care products, per and polyfluoroalkyl substances were studied for their presence in wastewater in Africa, Oceania, North America, Asia, Europe and South America. The highest concentration of pesticides in wastewater was recorded in Africa (Cameroun) at concentration ranging from 2 to 2993 ng/L whilst the least was recorded in Europe (Spain) at concentrations ranging from 0.02 to 1.94 ng/L; Pharmaceuticals and personal care products had the highest concentration in Africa (Egypt) at 70.6 to 119.4 mg/L whilst the least concentration was found at 0.1 to 646 ng/L in Africa (Tunisia); Per and polyfluoroalkyl substances had the highest concentration in Asia (Thailand) at 662 to 1383 ng/L while the least concentration was found to be in the range 0.2 to 48.6 ng/L in Europe (Denmark); Microplastics were also recorded in this study to have the highest concentration in the range 28.4 to 79.9 particles/L in Asia (China) and the least concentration in the range 0.0008 particles/L in North America (USA). Reliable analytical extraction and detection methods were the solid phase extraction and high-performance liquid chromatography coupled to different detectors respectively, and they were employed for the pesticides, pharmaceuticals and personal care products, per and polyfluoroalkyl substances only whilst the extraction and detection methods employed for the microplastics were filtration and digestion techniques followed by the FT-IR detection method. EPs were more prevalent in the African continent as a result of various socio-economic issues that led to poor sani
Keywords: African Research